Synergizing genome editing and cancer immunotherapy - Gabriel, Richard; Knipping, Friederike; Kalle, Christof von (Translational cancer research, 2017)
Cancer immunotherapy has recently become a powerful treatment option as several strategies harnessing the immune system to fight cancer achieved remarkable therapeutic benefits in clinical trials. Oncolytic viruses mediate selective tumor cell lysis (1), checkpoint inhibitors block receptors such as CTLA4 or PD1 on T cells and/or their ligands on tumor cells to reverse T cell suppression (2) and adoptive T cell therapy uses autologous tumor infiltrating lymphocytes (TIL) or genetically modified T cells to kill cancer cells. The latter has recently led to unprecedented efficacy, predominantly as a treatment for melanoma and leukemia. Similarly, gene editing—the precise modification of genes and genomic loci—holds enormous potential for clinical and research applications, primarily owing to the ease of use of the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPRassociated (Cas9) system that has transformed gene editing into a widely-used technique (3). Research efforts in both fields are currently combined by exploiting gene editing to enhance efficacy and safety of adoptive T cell therapies. In a recent edition of Nature, Eyquem and colleagues showed the superior potency of gene edited T cells in eliminating tumor cells and promoting survival (4).
Gesehen am 06.06.2018